Pembuatan Bioetanol Dari Tandan Kosong Kelapa Sawit Menggunakan Teknik Imobilisasi Sel Saccharomyces Cerevisiae - Nayandra Hazara Assyabil; Marlinda, Marlinda (UIR Press, 2025)
Empty palm fruit bunches (TKKS) are solid waste from palm oil mills that have the potential to be used as raw material for bioethanol due to their high cellulose content of 45.95%. This study aims to produce bioethanol from TKKS using Saccharomyces Cerevisiae cell immobilization techniques. The variables used are Saccharomyces Cerevisiae cell immobilization concentrations of 15% and 20% (w/v) and fermentation times (1, 2, 3, 4, and 5 days). TKKS that had undergone a delignification process with 10% NaOH was weighed at 15 grams, then hydrolyzed using eco enzyme and fermented together with a nutrient solution and immobilized Saccharomyces Cerevisiae cells. The immobilization of Saccharomyces Cerevisiae cells was carried out using 10% Na-Alginate and 7% CaCl2. The best results were obtained at a cell immobilization concentration of 20% (w/v) and a fermentation time of 3 days, with a bioethanol content of 27.2470% (v/v) and a yield of 23.7910% (w/w). These results indicate that the Saccharomyces cerevisiae cell immobilization technique can increase the efficiency of bioethanol fermentation from TKKS.